Electric field-induced transformations in bismuth sodium titanate-based materials. (October 2021) - Viola, Giuseppe; Tian, Ye; Yu, Chuying; Tan, Yongqiang; Koval, Vladimir; Wei, Xiaoyong; Choy, Kwang-Leong; Yan, Haixue
Abstract: Electric field-induced transformations occur in a myriad of systems with a variegated phenomenology and have attracted widespread scientific interest due to their importance in many applications. The present review focuses on the electric field-induced transformations occurring in bismuth sodium titanate (BNT)-based materials, which are considered an important family of lead-free perovskites and represent possible alternatives to lead-based compounds for several applications. BNT-based systems are generally classified as relaxor ferroelectrics and are characterized by complex structures undergoing various electric field-driven phenomena. In this review, changes in crystal structure symmetry, domain configuration and macroscopic properties are discussed in relation to composition, temperature and electrical loading characteristics, including amplitude, frequency and DC biases. The coupling mechanisms between octahedral tilting with polarization and strain, and other microstructural features are identified as important factors mediating the local and overall electric field-induced response. The role of field-induced transformations on electrical fatigue is discussed by highlighting the effects of ergodicity on domain evolution and fatigue resistance in bipolar and unipolar cycles. The relevance of field-induced transformations in key applications, including energy storage capacitors, actuators, electrocaloric systems and photoluminescent devices is comprehensively discussed to identify materials design criteria. The review is concluded with an outlook for future research.